The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1038/s41598-019-40392-1
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic stroke in mice induces lung inflammation but not acute lung injury

Abstract: Stroke is a major cause of death worldwide and ischemic stroke is the most common subtype accounting for approximately 80% of all cases. Pulmonary complications occur in the first few days to weeks following ischemic stroke and are a major contributor to morbidity and mortality. Acute lung injury (ALI) occurs in up to 30% of patients with subarachnoid haemorrhage but the incidence of ALI after ischemic stroke is unclear. As ischemic stroke is the most common subtype of stroke, it is important to understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…These changes were unlikely due to the spontaneous bacterial infection that reported in other studies . Consistent with our observations, recent studies have also shown that severe ischemic stroke in mice does not cause spontaneous bacterial infection . Using tMCAO model, Stanley et al showed that SAP is caused by the translocation and dissemination of commensal bacteria from the intestinal tracts to lungs, and SAP does not occur in mice housed in a germ‐free environment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These changes were unlikely due to the spontaneous bacterial infection that reported in other studies . Consistent with our observations, recent studies have also shown that severe ischemic stroke in mice does not cause spontaneous bacterial infection . Using tMCAO model, Stanley et al showed that SAP is caused by the translocation and dissemination of commensal bacteria from the intestinal tracts to lungs, and SAP does not occur in mice housed in a germ‐free environment.…”
Section: Discussionsupporting
confidence: 92%
“…3,15 Consistent with our observations, recent studies have also shown that severe ischemic stroke in mice does not cause spontaneous bacterial infection. 23 Using tMCAO model, Stanley et al 15 showed that SAP is caused by the translocation and dissemination of commensal bacteria from the intestinal tracts to lungs, and SAP does not occur in mice housed in a germ-free environment. These observations strongly suggest that the incidence of SAP is determined by the composition of gut microbiota, and this speculation is further supported by the fact that mice with different genetic backgrounds develop SAP with various severity.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of ACE2 levels within 24 h of brain injury suggests fast kinetics of signaling to induce protein expression changes in the lungs. The molecular mechanisms underlying this response in the lungs after transient MCAO are currently unclear, but, based on our data and related studies of others increased post-stroke lung inflammation might be a possible explanation (Austin et al, 2019). Physiologically, the augmented ACE2 levels in inflamed lungs after brain ischemia may help to counterbalance the subsequent inflammatory lung injury (Imai et al, 2005).…”
Section: Discussionmentioning
confidence: 58%
“…In addition, stroke patients may present signs of severe immunosuppression and inflammation that often lead to hospital-acquired respiratory infections (Shi et al, 2018). A recent study by Austin et al has demonstrated an increased number of mononuclear granulocytes in bronchoalveolar lavage fluid and higher IL-1 expression in lung tissue of mice that were subjected to ischemia-induced brain injury (Austin et al, 2019). In this respect, it is highly conspicuous that a plethora of clinical studies identified stroke as one of the most significant risk factors for a severe course of COVID-19 in humans (Bravi, 2020;Khawaja, 2020;Pigoga, 2020;Ssentongo, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Adrenergic and the HPA axis pathways act synergistically to induce splenic atrophy and natural killer (NK) cell deficiency in the periphery via coordinated effects of NE and GCs [4]. Moreover, ischemic stroke may cause a significant increase in bronchoalveolar lavage fluid macrophages and neutrophils and whole lung tissue proinflammatory IL-1β mRNA expression in experimental mice [5]. IL-1β is known to be involved in the development of acute lung injury (ALI) and/or acute respiratory distress syndrome and has been shown to be one of the most biologically active cytokines in ALI [5].…”
mentioning
confidence: 99%